The adventures of Captain Underpants : an epic novel - Pilkey, Dav, 1966- (New York : Scholastic, 1997)
When George and Harold hypnotize their principal into thinking that he is the superhero Captain Underpants, he leads them to the lair of the nefarious Dr. Diaper, where they must defeat his evil robot henchmen.
"A Little Apple paperback."
4.8
3-6.
3-6
English
Keywords: Captain Underpants (Fictitious character) -- Juvenile fiction; Heroes -- Juvenile fiction; School principals -- Juvenile fiction; Captain Underpants (Fictitious character) -- Fiction; Heroes -- Fiction; Humorous stories; School principals -- Fiction; Science fiction; Captain Underpants (Fictional character) -- Fiction; Heroes and heroines -- Fiction; Humorous fiction; School superintendents and principals -- Fiction; Science fiction; Humorous fiction; Science fiction